The HOPE Asia network 2022 up-date consensus statement on morning hypertension management - Kario, Kazuomi; Wang, Ji-Guang; Chia, Yook Chin *; Wang, Tzung-Dau; Li, Yan; Siddique, Saulat; Shin, Jinho; Turana, Yuda; Buranakitjaroen, Peera; Chen, Chen Huan; Cheng, Hao Min; Huynh, Minh Van; et al. (Wiley, 2022)
Morning hypertension is an important clinical target in the management of hypertension for perfect 24-h blood pressure (BP) control. Morning hypertension is generally categorized into two types: "morning surge" type and "sustained nocturnal and morning hypertension" type. The "morning surge" type is characterized by an exaggerated morning blood pressure surge (MBPS), and the "sustained nocturnal and morning hypertension" type with continuous hypertension from nighttime to morning (non-dipper/riser type). They can be detected by home and ambulatory blood pressure measurements (HBPM and ABPM). These two forms of morning hypertension both increase the risk of cardiovascular and renal diseases, but may occur via different pathogenic mechanisms and are associated with different conditions. Morning hypertension should be treated to achieve a morning BP level of < 135/85 mmHg, regardless of the office BP. The second target morning BP levels is < 125/75 mmHg for high-risk patients with morning hypertension and concomitant diseases. Morning hypertension is more frequently found in Asians, than in Westerners. Thus, the management of morning hypertension is especially important in Asia. The detection of morning hypertension and the individual home BP-guided treatment approach targeting morning BP in combination with ABPM, and the optimal treatment of morning hypertension would reduce cardiovascular events in Asia.